Clinical Research on Abdominal Acupuncture plus Conventional Acupuncture for Knee Osteoarthritis - 蒙吕荣 樊莉 符文彬 李勇 段树民（翻译） (Journal of Traditional Chinese Medicine, 2009)
To probe the therapeutic effect of abdominal acupuncture plus conventional acupuncture on knee osteoarthritis. Methods： PEMS3.1 software was used. The 105 patients with knee osteoarthritis were randomly divided into an abdominal acupuncture group, a conventional acupuncture group and a combined group （abdominal acupuncture plus conventional acupuncture）. For the abdominal acupuncture group, the abdominal acupuncture was performed at Zhongwan （CV 12）, Guanyuan （CV 4）, Wailing （ST 26）, Daheng （SP 15）, Lower Rheumatism point and Qipang with needles retained for 30 minutes. For the conventional acupuncture group, the acupuncture was practiced at Neixiyan （EX-LE4） and Dubi （ST 35） of the affected limb, Yanglingquan （GB 34）, Liangqiu （ST 34）, Xuehai （SP 10） and Xiyangguan （GB 33）. For the combined group, both methods were applied. Treatment was given once a day, 6 times a week, for 4 weeks. Lysholm knee scoring scale was used to score the functions of knee before and after treatment. Results： Of 35 cases in the abdominal acupuncture group, 8 cases were remarkably relieved, 10 cases relieved, 14 cases improved, and 3 cases failed, the total effective rate was 91.4%. Of 35 cases in the conventional acupuncture group, 7 cases were remarkably relieved, 8 cases relieved, 16 cases improved, and 4 cases failed, the total effective rate was 88.6%. Of 35 cases in the combined group, 13 cases were remarkably relieved, 16 cases relieved, 5 cases improved, and 1 cases failed, the total effective rate was 97.1%. There was a remarkable difference in the effect among 3 groups （P〈O.05）. The difference in scores of Lysholm knee scoring scale for knee joint after treatment among 3 groups was very significant （P〈0.01）. Conclusion： Abdominal acupuncture has reliable effect for knee osteoarthritis and it has the synergized function when combined with conventional acupuncture.